A Systematic Literature Review of Technopreneur Ship Fashion Design - Rahayu Purnama; Melly Prabawati; Vivi Radiona; Yeni Sesnawati; Rosita Mohd Tajuddin; Muhamad Aiman Afiq Mohd Noor (Malikussaleh University, Aceh, Indonesia, 2025)
The fashion industry requires Technopreneur fashion design to face the challenges of the technology and digitalization era in preparation for the 5.0 industrial age. Entrepreneurship dimensions, namely autonomy, innovativeness, risk-taking, proactive, and technology proficiency, are confident insufficient for Technopreneur ship due to their limited resources and lack of knowledge and access to foreign Technopreneur ship in fashion design. This study identifies and reviews the literature on Technopreneur ship orientation fashion education in Scopus between 2010 and 2025. This study identifies and reviews literature on technopreneurs’ orientation from scientific domains: entrepreneurial dimensions and entrepreneur-based technology drivers in fashion design. A systematic approach was adopted, recognizing 25 relevant articles from published journals indexed by Scopus collected from 2010 to 2025. The lack of literature on the technopreneur dimension has resulted in 10 dominant and representative articles originating from Scopus indexed journals and other related journals indexed by Google Scholar collected from 2002-2025. This study consists of two essential parts: 1) descriptive analysis, discussing the characteristics of the related articles, the country of the study, and the methods used. 2) thematic analysis, discussing the six essential categories of drivers in the adoption of technopreneurship and more deeply. The results regarding creating future ideas mean the same as autonomy, business innovation is innovation in the entrepreneurial dimension, seeking opportunities means being proactive, creating new businesses means the same as risk-taking, and technological proficiency are common expressions from several literatures regarding views on technopreneurship itself that do not originate from the entrepreneurial orientation that exists in the previous literature. This study proposes a conceptual framework of technopreneur orientation in fashion design education to develop a sustainable fashion design curriculum in the future.